Активація пуринергічних сигнальних шляхів під час розвитку запальних захворювань кишечника - Жеребятьєв, Олександр Сергійович; Войтович, Олександр Васильович; Матильонок, Тетяна Юріївна; Єгоров, Артем Анатолійович; Бурега, Ігор Юрійович; Жеребятьев, А. С.; Войтович, А. В.; Мотилeнок, Т. Ю.; Егоров, А. А.; Бурега, И. Ю.; Zherebyatiev, O. S.; Voitovich, O. V.; et al. (My University, 2020)
Запальні захворювання кишечника є хворобою з нечітким патогенезом, пов’язані з основними дефектами імунорегуляції слизової оболонки кишечника які розвиваються у генетично схильних осіб. Ці аномалії часто виникають у зв’язку з мікробним дисбіозом і приводять до необмеженого запалення кишечника та інших тканин. Це призводить до довготермінової захворюваності та, можливо, до смерті дорослих та дітей. Зменшення запалення та відновлення імунної толерантності при запальних захворюваннях кишечника залишаються головною терапевтичною метою. Проте, існуюча терапія запальних захворюваннях кишечника все ще значною мірою залежить від широкомасштабної імуносупресії. Наприклад, близько половини пацієнтів, які отримують антитіла проти TNF, демонструють суттєву клінічну відповідь. Ці поліпшення часто є самообмеженими, проте, на жаль, збільшується ризик опортуністичних інфекцій. Ектонуклеотидази зокрема сімейства CD39, мають значний вплив на динамічну рівновагу прозапального позаклітинного АТФ, нуклеотидів АДФ та імуносупресивного потенціалу аденозинуклеозидів. CD39 відіграє домінуючу роль у пуринергічній регуляції запалення судин, тромбозу та імунної відповіді у таких умовах. Воспалительные заболевания кишечника являются заболеваниями с нечетким патогенезом, связанными с основными дефектами иммунорегуляции слизистой оболочки кишечника, развивающихся у генетически предрасположенных лиц. Эти аномалии часто возникают в связи с микробным дисбиозом, и приводят к неограниченному воспалению кишечника и других тканей. Это приводит к долгосрочной заболеваемости и, возможно, к смерти взрослых и детей. Уменьшение воспаления и восстановление иммунной толерантности при воспалительных заболеваниях кишечника остаются главной терапевтической целью. Однако, существующая терапия воспалительных заболеваний кишечника все еще в значительной степени зависит от широкомасштабной иммуносупрессии. Например, около половины пациентов, получающих антитела против TNF, демонстрируют существенный клинический ответ. Эти улучшения часто являются самоограниченными, однако, к сожалению, увеличивается риск оппортунистических инфекций. Ектонуклеотидазы в частности семейства CD39, оказывают значительное влияние на динамическое равновесие провоспалительного внеклеточного АТФ, нуклеотидов АДФ и иммуносупрессивного потенциала аденозинуклеозидов. CD39 играет доминирующую роль в пуринергической регуляции воспаления сосудов, тромбоза и иммунного ответа в таких условиях. Inflammatory bowel disease is an important illness of unclear pathogenesis associated with major defects in mucosal immunoregulation and develops in genetically susceptible individuals. These abnormalities often occur in association with microbial dysbiosis and result in unfettered inflammation of the intestine and extraintestinal tissues. Such events result in long-term morbidity and possibly even death, in otherwise healthy adults and children. Dampening inflammation and re-establishing immune tolerance in inflammatory bowel disease remain the major therapeutic goal. However, existing inflammatory bowel disease therapies albeit providing recent advances, still largely rely on broad-based immunosuppression. For example, only around half of the patients treated with anti-TNF agents show substantive clinical responses. These improvements are often self-limited, while unfortunately increasing the risk of opportunistic infections. The purpose of the study was to investigate the control of mucosal immune responses, which are based on fundamental signaling pathways. Long-term interests in the regulation of purinergic signaling are now being leveraged to develop innovative and hopefully non-toxic therapies for inflammatory bowel disease. This review and the accompanying articles in this special issue address new therapeutic concepts in inflammatory bowel disease, as based on recent, linked work in hypoxia and purinergic signaling, mucosal barrier functions and microRNA biology. In several recent, comprehensive reviews, have already addressed the biological functions of ectoenzymes, such as CD39, CD73, and CD38, in the regulation of purinergic signaling and control of extracellular adenosine levels. Others, have noted the importance of these mechanisms in immunomodulation, as in cancer and inflammation. The ectonucleotidases of the CD39 family, in particular, have major impacts on the dynamic equilibrium of proinflammatory extracellular ATP, ADP nucleotides vs. the immunosuppressive potential of adenosine nucleosides. CD39 plays a dominant role in purinergic regulation of vascular inflammation, thrombosis, and the immune response in such settings.
Активация пуринергического сигнального пути во время развития воспалительных заболеваний кишечника
Activation of purinergic signaling pathways during the development of inflammatory bowel disease
Keywords: аденозин; АТФ; Е-НТФД-аза (екто-нуклеозидтрифосфатдифосфогідролаза); запальні захворювання кишечника; лімфоцити; Э-НТФД-аза (экто-нуклеозидтрифосфатдифосфогидролаза); воспалительные заболевания кишечника; лимфоциты; adenosine; ATP; E-NTPDase (ecto-nucleoside triphosphate diphosphohydrolase family); inflammatory bowel disease; lymphocytes